POTENTIAL FOR PRIVACY VIOLATIONS BY MOBILE APPLICATIONS: A LITERATURE REVIEW OF LEGAL STUDIES - Loso Judijanto (ADISAM PUBLISHER, 2025)
Mobile applications, with their ability to collect and process user data, raise significant privacy concerns. This literature study critically evaluates the risks of possible privacy violations and how applicable legal regulations address these issues. It was found that many applications fail to obtain clear consent from users and are often not transparent in their data collection and processing practices. In addition, sharing data with third parties without adequate safeguards increases the risk of data leakage. Through a legal perspective, this study emphasises the importance of transparency, data protection, and accountability of application developers in maintaining user privacy. This study underlines that a comprehensive approach to regulation and the strict application of privacy principles are essential to reduce the risk of violations and protect user rights